Simulation of tiltrotor maneuvers by a coupled multibody–mid fidelity aerodynamic solver - Cocco, A.; Savino, A.; Montagni, D.; Tugnoli, M.; Guerroni, F.; Palazzi, M.; Zanoni, A.; Zanotti, A.; Muscarello, V. (My University, 2020)
The present work proposes a new aeroelastic solution applicable to rotors and tiltrotors configuration by joining the multibody software MBDyn and the mid-fidelity aerodynamic tool DUST. The coupled MBDyn-DUST simulation environment is aimed to be used for the evaluation of the loads and of the vibratory levels of a tiltrotor aircraft during some critical transient maneuvers. The coupling is first validated by modelling the XV-15 equipped with metal blade rotors in hover configuration. Firstly, the dynamic behaviour of the rotor is tested by comparing the MBDyn Campbell collective diagram with the corresponding CAMRAD II and RCAS diagrams. Secondly, the rotor performances in hover are evaluated by using the coupled approach. The structural dynamics is taken from MBDyn whereas the aerodynamic loads are calculated by DUST. This coupled approach shows a good agreement in terms of polar curve and figure of merits when compared to experimental results. These preliminary results encouraged the use of this novel coupled tool for the simulation of tiltrotor flight dynamics and aeroelasticity.